Quality characteristics of bioactive iron and its supplementation in females of childbearing age - Abdullah, Muhammad; Mahmood, Shahid; Khalid, Naeem; Ahmed, Anwaar (Journal of Pure and Applied Agriculture, 2023)
An experiment was conducted using molasses (abundant waste material of the sugar industry) and synthetic sources of iron to evaluate storage stability, nutritional quality and sensory acceptability of different molasses based products. The blood of 787 pregnant, 862 non-pregnant and 862 lactating volunteers were examined for hemoglobin levels, where the frequency of anemic (Hb level less than 11 g/dL) was 38.00, 36.00 and 37.00 %, respectively. The blood samples investigated for other biological indicators marked them iron deficiency anemia (IDA). It was exhibited that 70.29 % pregnant, 65.92 % non-pregnant and 67.71 % lactating females were found to have IDA. During supplementation study, the significant effect of bioactive and synthetic iron against IDA among